The current update of Indonesian pharmacist challenges in antimicrobial stewardship: a scoping review - Sylraini, Mahfira Leily (BKM Public Health and Community Medicine, 2024)
Purpose: This study explores the current update of Indonesian pharmacist roles and challenges in dealing with antibiotic resistance. Method: PubMed and Scopus were used to search articles on related topics. Articles published within the last 5 years were selected for review. Three articles were found that are relevant to the topic and research question. Result: Hospital pharmacists and community pharmacists have a role in antimicrobial stewardship. In fulfilling their roles, pharmacists face various challenges. Hospital pharmacists face challenges such as lack of authority to provide intervention suggestions to doctors for preventing antibiotic resistance and less likely to have experience caring for a patient with a multidrug-resistant infection. On the other hand, community pharmacists also face challenges including patient demands for antibiotics, pressure to meet revenue targets, pressure from pharmacy owners, and less stringent regulations. Conclusion: Optimizing the role of pharmacists, especially hospital and community pharmacists, is necessary to reduce antibiotic resistance. Management approaches to enhance collaboration among healthcare professionals can be implement to address the challenges faced by hospital pharmacists. Meanwhile, providing regular patient education, engaging with pharmacy owners, and strengthening policies to reduce antimicrobial resistance can be strategies to reduce community pharmacists’ challenges.